Process-structure-property of additively manufactured continuous carbon fiber reinforced thermoplastic : an investigation of mode I interlaminar fracture toughness - Goh, Guo Dong (2022)
The process-structure-property (PSP) relationship of continuous carbon fiber reinforced thermoplastics manufactured through fused filament fabrication was investigated for the first time, specifically on mode I Interlaminar Fracture toughness (ILFT). A standard double cantilever beam test is used to evaluate the mode I ILFT. The PSP relationship is established using micro-computed tomography scan and laser optical microscope. This study demonstrates that higher nozzle, bed temperatures, and lower print speed enhances the mode I ILFT. The mode I ILFT is found to be greatly affected by porosity and bond formation between the layers, which are dependent on the process parameters.